Carbon Dioxide Adsorption on Grafted Nanofibrous Adsorbents Functionalized Using Different Amines - Abbasi, A. (Frontiers Media S.A., 2019)
Of late, the demand for new CO2 adsorbents with high adsorption capacity and stability is growing very fast. Nanofibrous adsorbents are potential materials for such application with most attempts made on carbon nanofibers. In this study, a series of electrospun nanofibrous adsorbents containing amines were prepared using a 3-stage promising approach and tested comparatively for CO2 capture. The preparation of adsorbents involved electrospinning of syndiotactic polypropylene (s-PP) solution, radiation-induced grafting (RIG) of glycidyl methacrylate (GMA) onto electrospun nanofibers, and functionalization of poly-GMA grafted s-PP nanofibrous mats with different amines, including ethanolamine (EA) diethylamine (DEA) and triethylamine (TEA). The effect of different amination parameters: namely, amine concentration, reaction time, temperature, and degree of grafting (DG) on the degree of amination (DA), was evaluated. The nanofibrous mats containing amine were tested for CO2 adsorption in a fixed bed column operated under various parameters such as amine density, amine type, initial CO2 concentration and temperature. The adsorbents recorded CO2 adsorption capacities of 2.87, 2.06, and 0.94 mmol/g for EA-, DEA- and TEA-containing adsorbents, respectively, at 30°C using initial CO2 concentration of 15. This was coupled with the same order of high amine efficiency of 75, 57, and 31. Results demonstrated that the nanofibrous adsorbent containing amine had strong potential for CO2 capture application. © Copyright © 2019 Abbasi, Nasef, Babadi, Faridi-Majidi, Takeshi, Abouzari-Lotf, Choong, Somwangthanaroj and Kheawhom.